مخالفات رخص البناء في التشريع الجزائري - ميساوي, خديجة (جامعة الوادي.University eloued, 2021)
"نلخص من خلال دراستنا لهذا الموضوع بأن مخالفات رخص البناء في مجال التهيئة والتعمير، ترجع أسبابها الى عدة عوامل وتتراوح العقوبات المقررة لها بحسب النصوص والمواد 77 من قانون 90/29 المتعلق بالتهيئة والتعمير والمرسوم 91/176. كما نلاحظ أن المشرع الجزائري قد سن العديد من النصوص القانونية تهدف الى تمكين الإدارة من ضبط حركة العمران وأن هذه الأجهزة الإدارية تتمتع بصلاحيات واسعة منحها المشرع سلطة المباشرة باتخاذ التدابير والإجراءات التي تحد من كل التجاوزات في هذا المجال. ""We summarize through our study of this topic that violations of building permits in the field of preparation and reconstruction are due to several factors، and the penalties prescribed for them range according to the texts and articles 77 of Law 90/29 related to preparation and reconstruction and Decree 91/176. We also note that the Algerian legislator has enacted many legal texts aimed at enabling the administration to control the movement of urbanization، and that these administrative bodies have broad powers granted by the legislator the authority to initiate measures and procedures that limit all abuses in this area. "
ماستر عقاري
Keywords: التشريع الجزائري -حركة العمران -التهيئة والتعمير